Comment on "Electron impact excitation and ionization cross section of tungsten ions, W44+" by El-Maaref et al. [J. Quant. Spectrosc. Radiat. Transfer 2019, 224:147]. (July 2019) - Aggarwal, Kanti M
Highlights: This comment shows that the recent published results of El-Maaref et al. for collision strengths for transitions in Zn-like tungsten ion, W XLV, are insufficient, incorrect and unreliable. Reported results of El-Maaref et al. for collision strengths are assessed to be overestimated by over two orders of magnitude. We also emphasize that a larger amount of data for W XLV, with much higher accuracy and covering a wider energy/temperature ranges, already exist in the literature. Abstract: In a recent paper, El-Maaref et al. [J. Quant. Spectrosc. Radiat. Transfer 2019, 224:147] have reported atomic data for Zn-like W XLV. Their results are mainly for energy levels, radiative rates, collision strengths (Ω) for electron impact excitation, and cross sections for ionization, but for only a few levels/transitions, and in a very limited range of energy. For the calculations of Ω they have adopted the DARC code. In this comment, through our independent calculations, we demonstrate that their results for Ω are highly underestimated by over two orders of magnitude, and hence are totally unreliable.